PsycEXTRA Dataset 1992
DOI: 10.1037/e478002004-001
|View full text |Cite
|
Sign up to set email alerts
|

Lapses in alertness: Brain-evoked responses to task-irrelevant auditory probes.

Abstract: SummaryThirteen subjects participated in an auditory simulation of a passive sonar target detection environment. Targets were 300 ms noise bursts presented at near threshold levels in a noise background at a mean rate of 10 per minute. Task-irrelevant probe tones were also presented

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

1993
1993
2015
2015

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 19 publications
2
8
0
Order By: Relevance
“…Operators' accuracy on vigilance tasks tends to decline with lower levels of proficiency and higher levels of workload [1]. Moreover, one study [14] finds that operators' performance gets discounted after a certain period of time, due to fatigue. Based on these facts, we model an operator's accuracy of steering sensors to capture high resolution imagery of targets as probability distributions that correlate with proficiency, workload, and fatigue.…”
Section: Modelingmentioning
confidence: 99%
See 1 more Smart Citation
“…Operators' accuracy on vigilance tasks tends to decline with lower levels of proficiency and higher levels of workload [1]. Moreover, one study [14] finds that operators' performance gets discounted after a certain period of time, due to fatigue. Based on these facts, we model an operator's accuracy of steering sensors to capture high resolution imagery of targets as probability distributions that correlate with proficiency, workload, and fatigue.…”
Section: Modelingmentioning
confidence: 99%
“…Similar trends can be found in other studies. One study of vigilance tasks found declining response rates after as little as 3 minutes of task performance, with response rates eventually plateauing at 70-80% of initial rates [14]. Di↵erences in task performance can also vary between operators.…”
Section: Introductionmentioning
confidence: 99%
“…Since the landmark investigations of Mackworth (1948), studies of alertness have confirmed that, on average, detection rates in laboratory tests begin to degrade after 2 to 3 rain of task performance, eventually reaching a plateau during which 70% to 80% of targets are detected (Makeig, Elliott, Inlow, & Kobus, 1990). While most vigilance research in the past has focused on measuring mean trends in performance.…”
Section: Introductionmentioning
confidence: 99%
“…While most vigilance research in the past has focused on measuring mean trends in performance. performance actually tends to fluctuate irregularly within sessions, with periods of several minutes of complete unresponsiveness not uncommonly observed (Makeig et al, 1990). During the last century, scattered studies have presented evidence for the presence of regular fluctuations in performance at cycle lengths ranging from a few seconds to several minutes for measures including time estimation, threshold detection, reaction time, and spontaneous speaking rate (Stroud, 1966).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation